2020
DOI: 10.1101/2020.05.02.073536
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Illuminating chromatin compaction in live cells and fixed tissues using SiR-DNA fluorescence lifetime

Abstract: The global compaction state of chromatin in a nucleus is an important component of cell identity that has been difficult to measure. We have developed a quantitative method to measure the chromatin compaction state in both live and fixed cells, without the need for genetic modification, using the fluorescence lifetime of SiR-DNA dye. After optimising this method using live cancer cell lines treated to induce chromatin compaction or decompaction, we observed chromatin compaction in differentiating epithelial ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 70 publications
(68 reference statements)
0
3
0
Order By: Relevance
“…FLIM on live interphase nuclei has shown chromatin decompaction upon chemical or radiation stimulus (Abdollahi et al 2018;Lou et al 2019;Pelicci et al 2019;Sherrard et al 2018). Live cell imaging studies have examined naive embryonic stem cells (ESCs) undergoing differentiation and showed that the presence of NANOG is essential for chromatin decompaction during pluripotency together with Rex1 downregulation (Hockings et al 2020). Furthermore, ATP depletion in ESCs leads to reduction in chromatin movement hindering transcription regulation during pluripotency (Hinde et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…FLIM on live interphase nuclei has shown chromatin decompaction upon chemical or radiation stimulus (Abdollahi et al 2018;Lou et al 2019;Pelicci et al 2019;Sherrard et al 2018). Live cell imaging studies have examined naive embryonic stem cells (ESCs) undergoing differentiation and showed that the presence of NANOG is essential for chromatin decompaction during pluripotency together with Rex1 downregulation (Hockings et al 2020). Furthermore, ATP depletion in ESCs leads to reduction in chromatin movement hindering transcription regulation during pluripotency (Hinde et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…We therefore investigated the effect FUS condensates might have on the level of euchromatin formation, which is strongly increased by hypomethylation. We have recently shown that the dye SiR-DNA (or SiR-Hoechst) can be used to determine the level of eu/heterochromatin formation in live cells (Hockings et al, 2020; Novo et al, 2022). As SiR-DNA intercalates with DNA structures, its fluorescence lifetime is significantly affected by the level of chromatin condensation.…”
Section: Resultsmentioning
confidence: 99%
“…As SiR-DNA intercalates with DNA structures, its fluorescence lifetime is significantly affected by the level of chromatin condensation. Since euchromatin formation is associated with significant DNA decondensation, an increase in the fluorescence lifetime of SiR-DNA can be associated with an increase in euchromatin formation (Hockings et al, 2020; Novo et al, 2022). We observe that both FUS mutant cells contain more euchromatin (i.e., more decondensed DNA), with P525L-FUS cells (3.44±0.03 ns) experiencing a greater extent of DNA decondensation than R495X-FUS cells (3.43±0.04 ns) and in comparison to the GFP control (3.40±0.03 ns) and WT-FUS cells (3.41±0.03 ns) ( Figure 3C&D ).…”
Section: Resultsmentioning
confidence: 99%